Morphine Withdrawal Enhances HIV Infection of Macrophages - Wang, Xu; Liu, Jinbiao; Zhou, Lina; Ho, Wen-Zhe (Frontiers in Immunology, 2019)
Opioid withdrawal reoccurs at high rates in opioid use disorder and compromises the immune system. In general, there are two types of opioid withdrawal: abrupt withdrawal (AW) and precipitated withdrawal (PW). In this study, we examined the effect of morphine AW or morphine PW on HIV infection of human blood monocyte-derived macrophages. We observed that both morphine AW and PW enhanced the susceptibility of macrophages to HIV infection. In addition, both AW and PW activated HIV replication in the latently infected myeloid cells (U1 and OM10.1). Investigation of mechanisms responsible for these observations showed that both AW and PW could inhibit the expression of multiple intracellular HIV inhibitory factors, including APOBE3G/F, SAMHD1, MX2 and HIV restriction microRNAs (miR-28, miR-125b, miR-150) in macrophages. These findings provide additional evidence to support the notion that opioid use inhibits the intracellular HIV restriction factors and enhances HIV infection and persistence in macrophages.